Efikasi Asap Cair dari Kayu Laban (Vitex pubescens) terhadap Rayap Coptotermes curvignathus - HA Oramahi; Purwati .; Sofian Zainal; Iskandar .; Idham .; Farah Diba; Wahdina . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2014)
ABSTRACTEfficacy of liquid smoke from laban wood (Vitex pubescens) against Coptotermes curvignathus. Antitermitic activities of liquid smoke produced from Vitex pubescens against C. curvignathus was evaluated in this study. This research was conducted in two steps, i.e. pyrolisis of liquid smoke and efficacy test of liquid smoke as antitermite. Three kinds of liquid smoke were produced at three different pyrolysis temperatures, i.e. 350 oC, 400 oC and 450 oC. Termiticidal activity was evaluated by a no-choice test. The research indicates that concentration of liquid smoke and pyrolysis temperatures significantly affected termite mortality and mass losses of the filter paper. The relationship between the concentration of liquid smoke (X) and termite mortality (Y) at 350 oC, 400 oC, and 450 oC were Y = 31,4 + 11,76X, (r2 = 0,60), Y = 30 + 11,86X (r2 = 0,59), and Y = 26,66 + 7,6X (r2 = 0,429). The relationship between concentration of liquid smoke (X) and mass losses (Y) at 350 oC, 400 oC, and 450 oC were Y= 85,12 -3,188X (r2 = 0,723), Y= 88,06 – 3,435X + (r2 = 0,953) and Y= 91,56 – 3,867X (r2 = 0,886).